2023
DOI: 10.3847/1538-4357/acac8f
|View full text |Cite
|
Sign up to set email alerts
|

Takeout and Delivery: Erasing the Dusty Signature of Late-stage Terrestrial Planet Formation

Abstract: The formation of planets like Earth is expected to conclude with a series of late-stage giant impacts that generate warm dusty debris, the most anticipated visible signpost of terrestrial planet formation in progress. While there is now evidence that Earth-sized terrestrial planets orbit a significant fraction of solar-type stars, the anticipated dusty debris signature of their formation is rarely detected. Here we discuss several ways in which our current ideas about terrestrial planet formation imply transpo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 222 publications
(290 reference statements)
0
6
0
Order By: Relevance
“…Grains 1 μm in radius will be ejected via radiation pressure force (Arnold et al 2019), exhibiting rapid drops in the infrared flux (Su et al 2019). Grains larger than the radiation blowout size would also drift outward radially with the aid of tenuous gas (Kenyon & Bromley 2016;Najita & Kenyon 2023). Larger grains will experience drag forces from the stellar wind (particularly important for young solar-like systems) and Poynting-Robertson drag.…”
Section: Origin Of High Collision Rate In the Inner Diskmentioning
confidence: 99%
See 2 more Smart Citations
“…Grains 1 μm in radius will be ejected via radiation pressure force (Arnold et al 2019), exhibiting rapid drops in the infrared flux (Su et al 2019). Grains larger than the radiation blowout size would also drift outward radially with the aid of tenuous gas (Kenyon & Bromley 2016;Najita & Kenyon 2023). Larger grains will experience drag forces from the stellar wind (particularly important for young solar-like systems) and Poynting-Robertson drag.…”
Section: Origin Of High Collision Rate In the Inner Diskmentioning
confidence: 99%
“…The gas could also originate from outgassing comets scattered toward the star, collisions of volatile-rich asteroids, or stripped atmospheres from giant impacts between protoplanets. Najita & Kenyon (2023) recently reviewed these processes and concluded that all of them are capable of generating 10 −3 -10 −2 M ⊕ of secondary gas for stars younger than a few hundred megayears. If the gas is secondary in origin, the ALMA CO gas limit (<10 −5 M ⊕ ) strongly disfavors a giant impact origin, as the estimated mass of the stripped atmosphere is on the order of 10 −4 M ⊕ for each giant impact (Najita & Kenyon 2023).…”
Section: The Origin Of the Gas Reservoirmentioning
confidence: 99%
See 1 more Smart Citation
“…Giant impacts may also explain the spatially unresolved, timevariable infrared excesses in ID8 (Meng et al 2014) and V488 Persei (Rieke et al 2021). Detecting catastrophic collisions occurring <10 au from the star was anticipated from simulations of terrestrial planet formation (Kenyon & Bromley2005; but see also Najita & Kenyon 2023 for ways to erase the signature of warm dusty debris).…”
Section: Introductionmentioning
confidence: 96%
“…Giant impacts may also explain the spatially unresolved, time-variable infrared excesses in ID8 (Meng et al 2014) and V488 Persei (Rieke et al 2021). Detecting catastrophic collisions occurring < 10 au from the star was anticipated from simulations of terrestrial planet formation (Kenyon & Bromley 2005; but see also Najita & Kenyon 2023 for ways to erase the signature of warm dusty debris).…”
Section: Introductionmentioning
confidence: 99%